O equity crowdfunding no Brasil: um estudo sobre as percepções iniciais de potenciais investidores - Vieira, Anderson Martins (2017)
Purpose – this dissertation had as a research problem to study the initial perceptions of potential investors in equity crowdfunding in the current Brazilian scenario. Design/Methodology – The methodology applied was qualitative, with semi-structured interviews using a non-probabilistic sample, with subjects who present two conditions: invested in stocks or any other securities and have notions of crowdfunding. The data were analyzed according to the technique of content analysis. Findings – The results obtained in the study point to high levels of positive perceptions regarding the concept of equity crowdfunding, the recent regulation of the subject, the limits of regulated investments and the possibility of investment through unions. There was a balance between negative and positive perceptions regarding the exemption from registration of the public offering and low compatibility between the period of return on investment desired by the participants and that verified in equity crowdfunding.investment through unions. The types of riches most perceived by clients in this type of investment were the risk of business failure or mismanagement, fraud risk and risk of information asymmetry. The most relevant factors most cited for long-term investment in this type of investment were identification with the project, the business plan and the financial return. And finally, the most relevant factors for the decision-making to invest in equity crowdfunding in the interviewees' view were the business plan and the sector of the economy in which the company carries out its activities. Research limitations – In addition to the limitations of the content analysis method, this study does not cover other crowdfunding modalities, nor does it seek to map the marketing potential or to analyze the institute deeply outside Brazil. Pratical implications – Equity crowdfunding has the potential to be a valuable tool for fundraising and investing in startups. Social implications – By approaching pickups and investors, equity crowdfunding can boost the emergence of startups, generating jobs and innovation. Originality – As far as we research, this is the first study conducted in Brazil that investigates the profile of potential investors in equity crowdfunding.